Developing The Potency of Productive Economy In IMKR Housewife Group Through The Making of Various Kinds of Wet and Dry Cakes - Rizabuana Ismail; Sismudjito Sismudjito; Eko Lase; Devi Sitohang (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
This PKM (Public Service) program was performed to increase the economic capacity of the service partners – women/wives who are under the IKMR (Railroad Track Young Family Association) at Lingkungan 12, Kelurahan Helvetia, Medan. Besides that, this activity also becomes an ideal need in encouraging the realization of socialpreneurship in lower class people. This activity was done through the penetration in various forms of making wet and dry cakes. It took 1 (one) month. It consisted of the presentation of marketing strategy and the training about making various kinds of wet and dry cakes. Besides the proposing team, this activity also involved some practitioners and graduate students in instilling the strengthening form to the partners. This service progressiveness included 1) the partners’ capacity to manage and use social capital as a marketing instrument, 2) the partners had the capacity to run online based-marketing system, and 3) the increase in the partners’ capacity to produce wet and dry cakes which had good taste